Perancangan Desain UI/UX Website E-Learning Berbasis Learning Management System dengan Metode Design Thinking - Hudha, Miftakhul; Haryono, Kholid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to develop a user interface (UI) and user experience (UX) design for a Learning Management System (LMS)-based e-learning platform for the Central Language Improvement (CLI) community at the Islamic University of Indonesia using the Design Thinking method. Following the empathize, define, ideate, prototype, and testing stages, this research involved administrators, mentors, and students in the development process. Data collection was conducted through direct observation and interviews, followed by analysis using user personas and mind mapping. Usability testing results showed good acceptance levels with Maze scores for Admin (75), Mentor (89), and Students (83), and a System Usability Scale (SUS) score of 75.2 indicating an